Increased Maternal Education and Knowledge of Nutrition and Reductions in Poverty are Associated with Dietary Diversity and Meal Frequency in an Observational Study of Indonesian Children - T. Crookston, Benjamin; Bennett, Cudjoe; Hall, P. Cougar; Hasan, Muhamad; Linehan, Mary; Syafiq, Ahmad; Torres, Scott; West, Joshua H.; Dearden, Kirk A. (International Journal of Child Health and Nutrition, 2018)
Background: Optimal infant and young child feeding during the first two years of life is essential to optimum child development and health. While the link between feeding practices and child health outcomes is well documented, little is known about the determinants of these feeding practices in Indonesia. The purpose of this study was to better understand factors associated with appropriate child feeding among Indonesian children 6–23 months of age. Methods: Interviewers conducted interviews with 1498 mothers of children 6–23 months of age to identify practices. Measures of feeding practices included dietary diversity, meal frequency, and minimum acceptable diet. Multivariate logistic regression was used to identify factors associated with dietary diversity and separately with meal frequency. Results: After adjusting for covariates, increased maternal education was associated with improved dietary diversity. Age of child [OR=1.11], knowledge of stunting [OR=1.80], and having ever received nutrition information [OR=1.89] were also associated with greater dietary diversity. Wealth [OR=0.86] and age of child [OR=0.92] were inversely associated with meal frequency. Maternal education, age of child, being a male child, knowledge of stunting, and having received nutrition information increased the odds of the child consuming a minimum acceptable diet. Conclusion: Increasing maternal education, knowledge of stunting, and knowledge of nutrition may improve dietary diversity while poverty alleviation has the potential to improve minimum meal frequency. These findings corroborate similar studies and confirm the importance of government efforts that help girls stay in school, improve families’ understanding of nutrition, and reduce poverty